Analisis Incident Management dan Service Desk Menggunakan Framework ITIL V4 pada Layanan KIR Dinas Perhubungan Kota Palembang - Andry Achmad Fadilla; Muhammad Rachmadi (Institut Agama Islam Negeri (IAIN) Curup, 2026)
The rapid development of information technology has encouraged government institutions to continuously improve the quality of digital-based public services, including vehicle inspection (KIR) services at the Palembang City Transportation Agency. Based on observations and interviews, several challenges were identified in the management of information technology services, including the absence of well-documented Standard Operating Procedures (SOPs), incident handling processes that are still carried out manually, and the suboptimal performance of service functions in responding to user complaints. This study aims to evaluate IT service management using the ITIL V4 framework, focusing on the Incident Management and Service Desk practices. The research methods employed include observation, interviews, questionnaire distribution to 17 respondents, maturity level analysis, gap analysis, RACI analysis, and SWOT analysis. The results indicate that the maturity level of Incident Management is 1.69, while Service Desk achieves a score of 1.54, both of which fall within the Repeatable level. Furthermore, the gap analysis reveals a difference of 0.31 for Incident Management and 0.46 for Service Desk compared to the targeted maturity level. The SWOT analysis also shows that the implementation of the KIR application has contributed positively to improving the efficiency of public services. However, several weaknesses remain, including the lack of standardized SOPs, the absence of a ticketing system, and a high dependency on vendors for IT service management. Based on these findings, the recommended improvements include the development of SOPs, implementation of a ticketing system, establishment of a more structured Service Desk function, and enhancement of IT personnel competencies. This study contributes by providing an ITIL V4-based IT service evaluation model integrated with RACI and SWOT analyses to support the improvement of digital public service quality within government institutions.